Pengaruh Komitmen terhadap Kepuasan Kerja Auditor: Motivasi sebagai Variabel Intervening (Studi Empiris pada Kantor Akuntan Publik di Jawa Timur) - Sri Trisnaningsih (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to empirically analyses the impact of organizational and professionalism commitment toward job satisfaction, and include motivation as intervening variable. The result of this research is expected to give contribution in developing the theory, especially concerning attitude of accountant. I addition, it is expected to give practical contribution for organization, especially public accountant.Path analysis was used to test the hypotheses using AMOS. The result reveals that (a) there is a significant effect between organizational and professional commitment and job satisfaction, (b) there is a significant effect between the organizational and professional commitment and motivation, (c) there is a significant effect between motivation and job satisfaction, (d) there is a significant indirect effect of the organizational and professional commitment toward job satisfaction, through motivation the intervening variable. The coefficient of direct effect of organizational and professional commitment is greater than that of  the indirect effect through motivation, the intervening variable. Therefore, motivation the intervening variable can be ignored.